Cognitive Approaches To Understanding Impersonal Sentences In English (Journal of Pedagogical Inventions and Practices, 2025)
This article explores impersonal sentence constructions in English through the lens of cognitive linguistics. Traditional syntactic perspectives often treat impersonal sentences as syntactic anomalies or exceptions. However, cognitive approaches provide insight into how such constructions reflect conceptualizations of agency, perspective, and information structure. The paper investigates different types of impersonal constructions, including weather expressions, passive structures, and extraposed subjects, and highlights how cognition and communicative intent influence their usage. The study also considers cross-linguistic insights and implications for second language acquisition